The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/srt.12174
|View full text |Cite
|
Sign up to set email alerts
|

Image analysis of skin color heterogeneity focusing on skin chromophores and the age‐related changes in facial skin

Abstract: We have developed evaluation methods for skin color heterogeneity by image analyses based on the major chromophores, melanin and hemoglobin, with special reference to their size. This methodology focusing on skin color heterogeneity should be useful for better understanding of aging and ethnic differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…Both, skin transparency and brown spots indicate a rapid change in the early 30s and the late 50s. The reports have described heterogeneity of the superficial skin color being dependent upon the size of pigmented spots and the hemoglobin content of the skin; however, age‐related heterogeneous changes within the epidermal layers have not been reported. These results suggest that the characteristics of age‐related skin color change differ between the upper and lower epidermal layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both, skin transparency and brown spots indicate a rapid change in the early 30s and the late 50s. The reports have described heterogeneity of the superficial skin color being dependent upon the size of pigmented spots and the hemoglobin content of the skin; however, age‐related heterogeneous changes within the epidermal layers have not been reported. These results suggest that the characteristics of age‐related skin color change differ between the upper and lower epidermal layers.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have described skin color heterogeneity as an age‐related change. Skin color heterogeneity results from the distribution of erythema and pigmentation and is more pronounced with aging . Kikuchi et al have revealed that the heterogeneity index of the melanin and hemoglobin on the skin surface increases with age.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly skin demonstrates age‐related changes, such as topographic effacement, deeper wrinkles, cosmetically unappealing skin color, alterations in the amount and integrity of dermal elastic tissue, elastosis, and cellular atypia (Kikuchi, Masuda, Yamashita, Kawai, & Hirao, ; Kikuchi et al, ; Warren et al, ; Zou, Song, & Jin, ). These age‐related alterations are the consequences of the intrinsic biologic clock and extrinsic aging effects, predominantly influenced by actinic damage (Bazin & Leveque, ; Warren et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Age‐related skin color changes occur through geographical distribution changes in erythema and pigmentation, influenced by diverse physical, chemical, and biological stimulation (Kikuchi et al, ). These age‐associated color changes are regarded as important cosmetic problems by many people and are considered to be fundamental to the advancement of dermatologic therapies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation